Fracture analysis of single layer Graphene sheets - Nguyen, Minh Ky (Journal of Technical Education Science, 2016)
The formula is derived analytically from the deformation and bending mechanism of sol- id-state carbon-carbon bonds to describe the mode I fracture of single layer graphene sheet (SLGS). Fracture of a single layer graphene is governed by the competition between bond breaking and bond rotation at a crack tip. It is demonstrated that in tension the cell walls bend and elongate, leading to the development of tensile stresses on some portions of the outer sur- faces of the cell walls. As a result it was found that fracture of graphene sheets can create frac- ture edges at the middle of bond and bond deformation and rupture are induced by the localized high stress near the crack tip.